1991
DOI: 10.1038/354494a0
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and transcriptional cooperation with Ha-Ras requires phosphorylation of c-Jun on serines 63 and 73

Abstract: Recent advances indicate a link between tumour promoters, transformation, and AP-1 activity. Protein kinase C activation increases AP-1 DNA-binding activity independently of new protein synthesis. AP-1 is also stimulated by transforming oncoproteins and growth factors. These proteins are thought to participate in a signalling cascade affecting the nuclear AP-1 complex composed of the Jun and Fos proteins. Because c-Jun is the most potent transactivator in the AP-1 complex and is elevated in Ha-ras-transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
596
5
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 763 publications
(631 citation statements)
references
References 19 publications
22
596
5
3
Order By: Relevance
“…Western blot analysis showed that M37 cells have elevated c-Jun protein levels, whereas AJ81 cells have no detectable c-Jun (Figure 3c). c-Jun is phosphorylated by JNK (Jun N-terminal kinase) at serines 63 and 73, which is necessary for its transactivation function (Smeal et al, 1991) but not its coactivation of AR (Wise et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Western blot analysis showed that M37 cells have elevated c-Jun protein levels, whereas AJ81 cells have no detectable c-Jun (Figure 3c). c-Jun is phosphorylated by JNK (Jun N-terminal kinase) at serines 63 and 73, which is necessary for its transactivation function (Smeal et al, 1991) but not its coactivation of AR (Wise et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been observed that functional Rac or CDC42 is required for the activation of JNKK-JNK signaling module, it has been observed that Ras is also involved in the activation JNK signaling pathway (Smeal, 1991, Minden et al, 1994Kyriakis et al, 1994). Recent studies indicate that in the speci®c instances in which Ras is involved in the activation of JNKK/JNK module, it appears that Rac or CDC42 is downstream of Ras mediating the`true' coupling (Coso et al, 1995;Minden et al, 1995).…”
Section: Map Kinase Kinase-4mentioning
confidence: 99%
“…The closely related m5 muscarinic receptor also transforms via a ras-dependent pathway (Mattingly et al, 1994). Mutationally activated MEK is su cient for cellular transformation and tumorigenesis (Mansour et al, 1994;Cowley et al, 1994), and Jun is required for transformation by ras (Smeal et al, 1991), thus it is possible that either MAPK or JNK pathways, or both together are utilized to elicit mitogenic responses. The ser/thr kinase raf has been implicated in transformation by m1 receptors (Crespo et al, 1994b), suggesting a MAPK mediated proliferative signal.…”
Section: Alpha1bmentioning
confidence: 99%